Executive coaching as a developmental tool: how it can help managers to improve their performance in their role as leaders - Peuthen, Clarissa (2020)
The use of executive coaching as leadership development approach for managers has significantly grown in organizations. Despite of this growth, empirical research in this field is limited. To address this limitation, this thesis was designed to contribute valuable empirical data by exploring executive coaching as a developmental tool and its effectiveness for managers to improve their role as leaders. A literature review addressing executive coaching and leadership development was conducted followed by qualitative research in the form of semistructured interviews with 12 German managers in leading positions who have undergone an executive coaching process with a focus on leadership development. The interviews investigated the coaching process, factors contributing to a successful coaching practice, benefits of executive coaching and leadership development. Overall research findings reveal that executive coaching is a good developmental tool for managers to be better leaders. Not only was leadership the area where executive coaching was most beneficial, it also enhances self-efficacy which is the precondition for leadership development. Other benefits of executive coaching were particularly found to be intra-personal and inter-personal. The key success factors for executive coaching are the coach’s ability to build a trustful environment and to be a good listener; the coachee's focus, internal motivation and willingness to change and work on themselves; a matching coaching relationship with open communication, no judgment and honesty; and an individualized coaching process.